Menakar Perbedaan Kurs Rupiah Terhadap Dolar Amerika Serikat dan Australia Sebelum dan Setelah PSBB WNA - Lusianus Heronimus Sinyo Kelen; Nur Asmy Abbas (Jurnal Manajemen dan Bisnis, 2021)
This study aims to analyze the difference in the exchange rate of the Indonesian rupiah against two foreign currencies: United States dollar and Australian dollar before and after large-scale social restrictions for foreign nationals as of January 1, 2021. The research method used in this thesis is quantitative research. with a descriptive approach. Using the exchange rates of the Indonesian Rupiah (IDR), United States Dollar (USD), and Australian Dollar (AUD) by obtaining data through the Bank Indonesia (BI) website, in the form of a January 2021 report. Analysis conducted on paired sample test, with research results showing no significant differences, it can be concluded that foreign exchange rates in each country are stable and improving